Learning in a time of division : school-university-community research in education - Reardon, R. Martin; Leonard, Jack (Current perspectives on school/university/community research., 2025)
US Secretary of Education, highlighted the "Raise the Bar: Lead the World" call to action that was then the slogan of US Department of Education in an interview hosted by The Atlantic. Cardona took part in a convening of "activists, policy makers, industry leaders, and pioneers" working to close multiple equity divisions across multiple indicators. While Cardona's focus during the interview was on the situation in the United States, the conditions for learning that he discussed surely resonate in international contexts in which dedicated educators are also keen to raise the bar and lead the world. Such an ambitious call to action would be challenging during a time of consensus, but our contemporary educational context both nationally and internationally is characterized by divisions of perspectives regarding the causes of and remedies for student achievement and discipline disparity, in addition to a raft of mental health and well-being issues. Further, there are unresolved concerns over who can teach what and to whom in the wake of legislative initiatives. One could be excused for suggesting that, in the contemporary field of education, we are uncertain about where we are and where we are going, but there is no shortage of ideas about what to do next. The authors whose work are showcased in Learning in a Time of Division: School-University-Community Research in Education share the ways in which their practice as educators has enshrined viable ideas about how to bridge divisions and facilitate learning, thereby contributing to reuniting a polarized world.